Antidiabetic activity of Solanum torvum fruit extract in streptozotocin-induced diabetic rats - Satyanarayana, Namani; Chinni, Suresh V.; Gobinath, Ramachawolran; Sunitha, Paripelli; Uma Sankar, Akula; Muthuvenkatachalam, Bala Sundaram (Frontiers in Nutrition, 2022)
Background: Solanum torvum Swartz, a medicinal plant belonging to the family Solanaceae, is an important medicinal plant widely distributed throughout the world and used as medicine to treat diabetes, hypertension, tooth decay, and reproductive problems in traditional systems of medicine around the world including Malaysia. The objective of the present study is to investigate hypoglycemic, antilipidemic, hepatoprotective activities, histopathology of the pancreas and specific glucose regulating gene expression of the ethanolic extract of S. torvum fruit in streptozotocin-induced diabetic Sprague- Dawley rats. Methods: Acute toxicity study was done according to OECD-423 guidelines. Diabetes was induced by intraperitoneal (i.p.) injection of streptozotocin (55 mg/kg) in male Sprague-Dawley rats. Experimental diabetic rats were divided into six different groups; normal, diabetic control, and glibenclamide at 6 mg/kg body weight, the other three groups of animals were treated with oral administration of ethanolic extract of S. torvum fruit at 120,160 and 200 mg/kg for 28 days. The effect of ethanolic extract of S. torvum fruit on body weight, blood glucose, lipid profile, liver enzymes, histopathology of pancreas, and gene expression of glucose transporter2 (slc2a2) and phosphoenolpyruvate carboxykinase (PCK1) was determined by RT-PCR. Results: Acute toxicity studies showed LD50 of ethanolic extract of S. torvum fruit to be at the dose of 1600 mg/kg body weight. Blood glucose, total cholesterol, triglycerides, low-density lipoproteins, very low-density lipoproteins, serum alanine aminotransferase, and aspartate aminotransferase were significantly reduced whereas high-density lipoproteins were significantly increased in S. torvum fruits (200 mg/kg) treated rats. Histopathological study of the pancreas showed an increase in number, size, and regeneration of β-cell of islets of Langerhans. Gene expression studies revealed the lower expression of slc2a2, and PCK1 in treated animals when compared to diabetic control. Conclusions: Ethanolic extract of S. torvum fruits showed hypoglycemic, hypolipidemic, and hepatoprotective activity in streptozocin-induced diabetic rats. Histopathological studies revealed regeneration of β cells of islets of Langerhans. Gene expression studies indicated lower expression of slc2a2, PCK1 in treated animals when compared to diabetic control, indicating that the treated animals prefer the gluconeogenesis pathway.